The Role of Emotional Creativity and Self-Disclosure in Post-traumatic Growth Among Healthcare Workers After the COVID-19 Pandemic - Iqbal, Anwar; Utami, Muhana Sofiati (Jurnal Psikologi, 2024)
Previous studies have shown that healthcare workers experienced post-traumatic growth (PTG) during the COVID-19 pandemic. Various factors, such as social support, coping strategies, and deliberate rumination, were also reported to positively influence healthcare workers’ PTG. This study examined the role of emotional creativity and self-disclosure in the PTG of healthcare workers handling COVID-19 patients. The study involved 186 healthcare workers recruited through convenience sampling. The Post-Traumatic Growth Inventory - Expanded (PTGI-X), Revised Self-Disclosure Scale (RSDS), and Emotional Creativity Inventory (ECI) were used to collect data in this study. Based on multiple regression analyses, the model consisting of emotional creativity and self-disclosure was able to predict PTG (F = 15.54; p < 0.001). Partially, the results indicated that emotional creativity significantly predicted PTG (β= 0.337; 95% CI = 0.198 - 0.477), whereas self-disclosure did not (β = 0.112; 95% CI= -0.027 - 0.251). Additional analyses showed that healthcare professionals with more than 20 years of working experience had significantly higher PTG than those with 11 – 20 years of working experience. This study implies that flexibility in expressing emotions is a more preferred and impactful psychological resource in helping healthcare workers face similar traumatic events in the future.